2005
DOI: 10.2337/diacare.28.3.533
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Subcutaneous Insulin Infusion (CSII) of Insulin Aspart Versus Multiple Daily Injection of Insulin Aspart/Insulin Glargine in Type 1 Diabetic Patients Previously Treated With CSII

Abstract: OBJECTIVE -Multiple daily injection (MDI) therapy of bolus insulin aspart and basal insulin glargine was compared with continuous subcutaneous insulin infusion (CSII) with aspart in type 1 diabetic patients previously treated with CSII.RESEARCH DESIGN AND METHODS -One hundred patients were enrolled in a randomized, multicenter, open-label, crossover study. After a 1-week run-in period with aspart by CSII, 50 subjects were randomly assigned to MDI therapy (aspart immediately before each meal and glargine at bed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
3
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 180 publications
(124 citation statements)
references
References 17 publications
3
115
3
3
Order By: Relevance
“…Adult patients with type 1 diabetes mellitus-meta-analysis Of 17 selected studies we had to exclude five studies from this meta-analysis for the following reasons: (1) one study did not report any HbA 1c baseline and follow-up data [13]; (2) one study compared only treatment sequences (CSII-MDI vs MDI-CSII) at study endpoint [24]; (3) another trial provided no measure of variability [37]; (4) in one study [36] the discrepancies in the measurement of variability could not be resolved; and (5) another study [32] had an unacceptably high dropout rate immediately after randomisation assignment. Ultimately, 12 studies were included in the meta-analysis of the percentage of glycated haemoglobin at the end of treatment.…”
Section: Glycaemic Control-glycated Haemoglobinmentioning
confidence: 99%
See 4 more Smart Citations
“…Adult patients with type 1 diabetes mellitus-meta-analysis Of 17 selected studies we had to exclude five studies from this meta-analysis for the following reasons: (1) one study did not report any HbA 1c baseline and follow-up data [13]; (2) one study compared only treatment sequences (CSII-MDI vs MDI-CSII) at study endpoint [24]; (3) another trial provided no measure of variability [37]; (4) in one study [36] the discrepancies in the measurement of variability could not be resolved; and (5) another study [32] had an unacceptably high dropout rate immediately after randomisation assignment. Ultimately, 12 studies were included in the meta-analysis of the percentage of glycated haemoglobin at the end of treatment.…”
Section: Glycaemic Control-glycated Haemoglobinmentioning
confidence: 99%
“…Adult patients with type 1 diabetes mellitus Of 14 studies reporting total insulin requirements at the end of treatment, 12 [13,19,22,24,28,30,[33][34][35][36][37]39] consistently found that the insulin doses were lower in CSII-treated patients. In seven [13,19,22,30,35,36,39] of these investigations, the difference was statistically significant.…”
Section: Total Insulin Requirementsmentioning
confidence: 99%
See 3 more Smart Citations